PERSECUTION AND MARTYRDOM OF CHRISTIANS IN THE ROMAN EMPIRE FROM AD54 TO 100: A LESSON FOR THE 21ST CENTURY CHURCH - Emeka C. Ekeke (European Scientific Journal, ESJ, 2012)
Persecution and martyrdom among adherents of various religions of the world have been a critical issue. In some religions it is honored and given a prominent place and the martyrs seen as having gone to paradise. In others they go as far as killing themselves in their bid to be seen as martyrs and inherit a place of prominent in the world to come. This study examined persecutions and martyrdom among Christians in the Roman Empire between AD 54 and AD100. It traces the history of persecution of Christians from the time of Emperor Nero to Domitian. The paper also traces brief biography of some emperors and their achievements within the period. The paper concludes with a lesson for the 21st century church. It recommends among others that Christians today should return to the kind of dogged faith that characterized the early Christians that made them grow in number and in strength. They should not resort to retaliation as has been the case in many instances but to turn vengeance to God if they are to be seen and known as Christians indeed.